Formation of inflation expectations: Does macroeconomic and policy environment matter? - Eda Gülşen; Hakan Kara (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
This paper investigates the changing behavior of inflation expectations in response to the macroeconomic and policy environment. Using a panel of professional forecasters covering thirteen years of inflation targeting period from Turkey, we present evidence on the behavioral shifts in the inflation expectations associated with evolving macroeconomic and policy performance. We use a unique survey with the feature of including matched policy rate and fixed-horizon inflation expectations at the individual level, therefore enabling to estimate the impact of monetary policy surprises on inflation expectations without reliance on strong identifying assumptions. Moreover, we employ a novel technique where direct feedback from survey respondents is used to determine the baseline empirical model governing expectations dynamics. Interpretation of the empirical findings joint with the direct feedback results from the survey indicate that the anchoring power of inflation targets depend on the policy performance. The weights attached to inflation targets in forming expectations are strongly associated with the size of the inflation deviation from the targets. When the targets no longer serve as a strong anchor, the survey participants assign increasingly higher weight to past inflation and the relationship between exchange rates and inflation expectations becomes stronger. Overall, our results imply that expectations behavior display significant and rapid shifts with the underlying economic and policy performance.
Keywords: C51; C53; E31; E37; E58; 330; Inflation expectations; Monetary policy; Inflation; Survey data